Corrosão de aço carbono em concretos microbiologicamente afetados - Coelho, Sheyla Ferreira Lima (2015)
Concrete corrosion is an important issue responsible for incalculable damage and excessive costs recovery. Regarding to microbial corrosion, it is upmost to understand how active is the influence of microorganisms on the corrosion of metal armors susceptible to its attack and how effective is the contribution of biopolymers on corrosion inhibition. The addition of biopolymers such as chitosan has demonstrated efficiency controlling the armor corrosion caused by chlorides diffusion, however its effect has not been tested on biocorrosion prevention yet. Based on that, this study aimed to investigate the effect of chitosan addition on microbiological corrosion of carbon steel CA-50 and CA-25 on a simulated solution and on concrete. Mass loss tests to calculate corrosion's electrical current and potential difference measures were used to assess the corrosion of carbon steel CA-25 and CA-50-proof test specimens, and steel and concrete specimens, in the presence and absence of chitosan, to the action of the following microorganisms: Escherichia coli, Pseudomonas aeruginosa, Mucor rouxii, Aspergillus niger, Penicillium oxalicum, and Fusarium solani. Concrete with steel CA 50 enhanced with chitosan without microrganisms exposure showed inhibitory effect of chitosan on chlorides exposure. The tests with chitosan in the middle of simulated concrete without addition of microorganisms show chitosan as a good corrosion inhibitor for chlorides, mainly for steel CA 50. E.coli presented itself as a promoter of the carbon steel corrosion, with maximized effect in the presence of chitosan. P. aeruginosa was revealed as the only microorganism which did not aggravate corrosion in any of the treatments tested and showed a surprising effect corrosion inhibitor in the absence of chitosan. As for filamentous fungi, while the M. rouxii did not cause corrosion behavior change on carbon steel, others have shown increased corrosion electrical current in the presence of chitosan in a simulated concrete solution. In turn, F. solani and P. oxalicum showed inhibitory effect for carbon steel corrosion (80 and 70%, respectively) when in the absence of chitosan. The same strains were used to evaluate corrosion on steel test specimens (C25) immobilized on concrete by the open-circuit potential technique. Except the A. niger, filamentous fungi and bacteria showed no evidence of interference in steel's corrosive process, regardless of the presence of chitosan. These results allow to observe the safety of the use of chitosan as carbon steel corrosion inhibitor on concrete, at least from the point of view of corrosion inducing effect by these microorganisms.